English Teacher Performance in Teaching at SMAN 3 Palopo - Utami, Nina (FOSTER: Journal of English Language Teaching, 2020)
This thesis focused on the research questions is how the English Teacher performance in teaching, include: how the planning of the teacher before teaching, how the strategies of the teacher in teaching, and constraints that affect teacher performance in teaching at SMAN 3 Palopo. The data were collected through observation, interviews, and documents, and were analyzed using qualitative descriptive techniques. The object of the research was the teacher of SMAN 3 Palopo, who has been certified. The research analyzed the data that has been found by observation, and the result was explained in the discussion. The results showed that the performance of English teachers in teaching at SMAN 3 Palopo was quite good. Saw from his readiness before teaching, the selection of strategies and methods that were suitable, as well as how to deal with all the obstacles that exist.